The Political Economy of Environmental Goods and Services: An Economic Nationalist Perspective - Oscar Ugalde Hernández (Economía y Sociedad, 2025)
Since the launch of the Doha Development Round in 2001 and its subsequent Ministerial Declaration, the call has been made to member countries of the World Trade Organization (WTO) to develop negotiations to reduce or eliminate tariff and non-tariff barriers to environmental goods and services. However, multilateral consensus between countries has been very complex to achieve.